CONSTRUCT DESIGN DEVELOPMENT OF ROBOTIC HAND ACTUATOR FOR AFTER STROKE PATIENT REHABILITATION - Gunawan Alim; Suryani Alifah; Arief Marwanto (Universitas Islam Sultan Agung, 2020)
This research is analyzing about construct design development of robotic hand actuator for after stroke patient rehabilitation, implementation for people paralyzed due stroke, the function is to move a paralyzed hand member. It consists of 12 actuators, and for each actuator is driven by DC Motor idependently. This actuator is movements by the other normal hand of stroke patient with symmetrical movements, asymmetry as well some physiotherapy movements that have been programmed. This integration control is carried out using an Arduino Uno microcontroller. The testing of the instrument was carried out by simulating the Simulink test, simulation testing using Proteus and direct testing of the prototype. This research have some diviations, and it happen because of the inertia of tools and equipment. This finding of this research is that robotic hand is quite heavy, and some movements that arise is not according in the program, and the response time is take a long time.